Food avoidance among breastfeeding mothers in Myanmar and its impacts on maternal dietary quality - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
Key Findings • This study designed and analyzed two new surveys in Myanmar. The first one is the fifth Myanmar Household Welfare Survey (MHWS) round conducted from April to June 2023, in which 12,953 respondents were surveyed, including 5,512 women of reproductive age (15-49). The second is the Rural Urban Food Security Survey conducted in 2020, in which respondents were women who were pregnant in round 1 (June-July 2020) in Yangon and participated in at least five of those six rounds. • Forty percent of all Myanmar women aged 15-49 believe that breastfeeding mothers should avoid at least one healthy food, with vegetables the most widely cited food to be avoided, followed by fruits, fish, meat and beans/nuts. • Beliefs were prevalent throughout Myanmar’s diverse regions and across both genders, but more common in majority Buddhist regions (and less common in majority Christian regions). • Beliefs in food avoidance during breastfeeding were less prevalent among women with more formal education and nutritional knowledge, and with exposure to nutrition counselling from community health workers. • Mothers in the Yangon panel saw minimum dietary diversity of women (MDD-W) fall by 46 percentage points from pregnancy to the first month after birth, stemming from significant declines in eight of the ten MDD-W food groups. • MDD-W recovered somewhat over the second to fifth months after birth but was still significantly lower up to the sixth month after birth.